Menstrual hygiene awareness, management and challenges among adolescent girls in rural areas in Ambala, India - Thaman, Varidhi; Mittal, Anjana; Chitkara, Ishika; Chahal, Prerna (International Journal Of Community Medicine And Public Health, 2021)
Background: The present study was undertaken to encourage articulation of needs and problems of adolescent school girls in rural areas in Ambala district, India, advancing good menstrual hygiene and generating evidence on menstrual hygiene awareness, management and challenges. Methods: This study was an observational cross-sectional study, conducted from July to September 2018, in two rural schools (school 1 and school 2) in Ambala, Haryana, India. A structured pre validated questionnaire was administered to the group of participating girl subjects of 11- 17 years; the questionnaire was explained to them, followed by a short animated film ‘Mythri’ in Hindi of 20 minutes imparting knowledge on MHM. The data was analyzed and the report was presented to the schools with recommendations. Results: We observed better MHM facilities in school 2 than school 1. Provision of good infrastructure and MHM facilities in schools, reduces the absenteeism of girls during menstruation. A statistically significant difference in girl students absenteeism for an average of 2.15 (66.66%) days/ month in school 1, and an average of 1.44 (21.05%) days/month in school 2 is reported. Sanitary pads usage of 50%-83% girls is reported; this may probably be because of percolation of information and knowledge about good hygienic ways. Disposal of absorbent material still poses a big issue. Social taboos were reported by 84.44% girls in school 1 and by only 32.89% girls in school 2. Conclusions: The insights from our study suggests a better MHM education in schools to create more awareness, judicious allocation of resources in schools, providing better infrastructure and basic support to manage menses effectively and with dignity.